Mucinous carcinoma in a male breast with skin ulcer: a case report - Lin, Xiaohui; Liao, Tingting; Yang, Yuting; Zhou, Jingzhi; Ma, Jie (Frontiers in Oncology, 2025)
A case of pure mucinous carcinoma of the male breast presenting with skin ulceration was reported. The patient, a 67-year-old male, inadvertently discovered a subcutaneous mass with the size of a soybean near the areola on the right side of his chest. Pathological analysis identified the mass as mucinous adenocarcinoma. Differentiating between primary mucinous carcinoma of the skin and mucinous carcinoma of the breast was challenging due to their overlapping histological and immunohistochemical features. Ultimately, the tumor was diagnosed as pure mucinous carcinoma of the male breast based on the primary site and clinical history.